The influence of particle size and static magnetic fields on the uptake of magnetic nanoparticles into three dimensional cell‐seeded collagen gel cultures. Issue 6 (31st October 2014) - Lewis, Emily E. L.; Child, Hannah W.; Hursthouse, Andrew; Stirling, David; McCully, Mark; Paterson, David; Mullin, Margaret; Berry, Catherine C.
Abstract Over recent decades there has been and continues to be major advances in the imaging, diagnosis and potential treatment of medical conditions, by the use of magnetic nanoparticles. However, to date the majority of cell delivery studies employ a traditional 2D monolayer culture. This article aims to determine the ability of various sized magnetic nanoparticles to penetrate and travel through a cell seeded collagen gel model, in the presence or absence of a magnetic field. Three different sized (100, 200, and 500 nm) nanoparticles were employed in the study. The results showed cell viability was unaffected by the presence of nanoparticles over a 24‐h test period. The initial uptake of the 100 nm nanoparticle into the collagen gel structure was superior compared to the larger sized nanoparticles under the influence of a magnetic field and incubated for 24 h. Interestingly, it was the 200 nm nanoparticles, which proved to penetrate the gel furthest, under the influence of a magnetic field, during the initial culture stage after 1‐h incubation. © 2014 The Authors. Journal of Biomedical Materials Research Part B: Applied Biomaterials Published by Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1294–1301, 2015.